(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The photometric method of recording enzyme activity is the most widely used in ELISA. In this case, enzyme substrates are substances whose transformation products are colored compounds or, conversely, the color of the substrates themselves changes during the reaction. Colored compounds absorb visible light, i.e. electromagnetic radiation with wavelengths of 400-700 nm. Light absorption obeys the Bouguer-Lambert-Bera law, according to which the optical density of a solution in a certain range is directly proportional to the concentration of the substance. A spectrophotometer is used to measure the optical density [3,5].